2019
DOI: 10.1002/adhm.201900260
|View full text |Cite
|
Sign up to set email alerts
|

Beyond 1000 nm Emission Wavelength: Recent Advances in Organic and Inorganic Emitters for Deep‐Tissue Molecular Imaging

Abstract: In vivo second near‐infrared (NIR‐II, 1.0–1.7 µm) bioimaging , a rapidly expanding imaging tool for preclinical diagnosis and prognosis, is of great importance to afford precise dynamic actions in vivo with high spatiotemporal resolution, deeper penetration, and decreasing light absorption and scattering. In the course of preclinical practices, organic and inorganic emitters with NIR‐II signals are indispensable keys to open the invisible biological window. In this review, NIR‐II emitters, including but not li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
77
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(81 citation statements)
references
References 115 publications
0
77
0
Order By: Relevance
“…18,19 Over the past several years, uorescence based imaging in the second near-infrared channel (NIR-II, 1000-1700 nm) has gained attention for its prominent merits and surpasses the conventional visible/NIR-I channels (700-900 nm) in terms of lower tissue scattering and minimal auto-uorescence, thus leading to signicant advances in imaging qualities including image depth and spatiotemporal resolution. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] More recently, based on a benzobisthiadiazole (BBTD) acceptor, a series of small molecular dyes with a donor-acceptor-donor (D-A-D) architecture have been developed. The reduced energy gap between the hybridized highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) levels in these molecular systems shied the uorescence emission spectrum from the NIR-I region to the NIR-II channel.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Over the past several years, uorescence based imaging in the second near-infrared channel (NIR-II, 1000-1700 nm) has gained attention for its prominent merits and surpasses the conventional visible/NIR-I channels (700-900 nm) in terms of lower tissue scattering and minimal auto-uorescence, thus leading to signicant advances in imaging qualities including image depth and spatiotemporal resolution. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] More recently, based on a benzobisthiadiazole (BBTD) acceptor, a series of small molecular dyes with a donor-acceptor-donor (D-A-D) architecture have been developed. The reduced energy gap between the hybridized highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) levels in these molecular systems shied the uorescence emission spectrum from the NIR-I region to the NIR-II channel.…”
Section: Introductionmentioning
confidence: 99%
“…F luorescence imaging in the second near-infrared region (NIR-II, 1000-1700 nm) enables direct visualization and real-time feedback of deep biological structures with a miraculous degree of clarity than NIR-I (800-900 nm) due to further suppressed photon scattering and minimized autofluorescence [1][2][3][4][5][6][7] . Simulation and experimental results have revealed that the imaging performance in term of spatial and temporal resolution and penetration depth could be further enhanced by the NIR-IIb (1500-1700 nm) fluorophores due to almost zero autofluorescence and much lower photo scattering [8][9][10] .…”
mentioning
confidence: 99%
“…The global burden of the most common and aggressive brain tumor in adults, i.e., glioblastoma, is already enormous, and an exponential increase is predicted for the next couple of decades. [64][65][66][67][68] Based on these challenges, U87MG tumor-bearing mice were established to assess the in vivo theranostic potential of PSY, and a clinically approved anticancer drug, cisplatin, was set as a positive control. The NIR-II uorescence signal at the U87MG tumor region was observed clearly within 24 h postinjection ( Fig.…”
Section: Resultsmentioning
confidence: 99%